2017
DOI: 10.1108/ijqrm-07-2015-0096
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of Six Sigma, Lean and Lean Six Sigma research publications in last two decades

Abstract: Quantitative analysis of Six Sigma, Lean and Lean Six Sigma research publications in last two decades Purpose-This research study intends to extend previous studies to a hybrid analysis of three business improvement practices of Lean, Six Sigma and Lean Six Sigma (LSS) within last two decades and identify the research gaps and focuses in more comprehensive and robust classification framework. Design/methodology/approach-A secondary data collection and literature review was conducted to collect information abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 74 publications
(130 reference statements)
4
38
0
1
Order By: Relevance
“…The distinct barriers in the Indian context are lack of knowledge, lack of resources, and lack of data (Bhat et al, 2014). Despite the growing interest and success of Six Sigma in the industry, the implementation in developing countries does not seem to be satisfactory (Alsmadi et al, 2012;Shokri, 2017). A literature review article by Shokri (2017) reviewed 591 Six Sigma articles over two decades .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The distinct barriers in the Indian context are lack of knowledge, lack of resources, and lack of data (Bhat et al, 2014). Despite the growing interest and success of Six Sigma in the industry, the implementation in developing countries does not seem to be satisfactory (Alsmadi et al, 2012;Shokri, 2017). A literature review article by Shokri (2017) reviewed 591 Six Sigma articles over two decades .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the growing interest and success of Six Sigma in the industry, the implementation in developing countries does not seem to be satisfactory (Alsmadi et al, 2012;Shokri, 2017). A literature review article by Shokri (2017) reviewed 591 Six Sigma articles over two decades . The article highlighted the fact that major part of Six Sigma research is done in the USA and UK and mainly focused on tools and techniques, DMAIC methodology, and success factors as compared to challenges.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Few studies are found on barriers or deficiencies in implementing Six Sigma, and specifically, the empirical studies are scant (Lande et al, 2016). Also, the studies on challenges in implementation are typically case studies (Shokri, 2017) which limit the generalisation of results (Nonthaleerak and Hendry, 2008). Earlier studies in Six Sigma show the influence of individual constructs on project success (Ribeiro et al, 2015;Sin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Fruto de uma crescente pressão dos clientes para a promoção do melhoramento da qualidade dos produtos, essas duas últimas décadas presenciaram um claro crescimento e difusão de abordagens gerenciais que visam o melhoramento dos processos produtivos. Nesse contexto, muitas empresas implementaram o sistema de produção Lean (SHOKRI, 2017). Inicialmente, esta filosofia de produção foi amplamente utilizada no setor de manufatura (LEWIS, 2000).…”
Section: Introductionunclassified